2014
DOI: 10.1111/aos.12496
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of persistent subepithelial corneal infiltrations on the visual performance and corneal optical quality after epidemic keratoconjunctivitis

Abstract: ABSTRACT.Purpose: Aim was to measure the effect of persistent subepithelial corneal infiltrates (SEIs) after epidemic keratoconjunctivitis (EKC) on visual performance and corneal optical quality. Methods: We examined 53 patients divided into two groups. Patients with previous EKC constituted the study group (Group 1, n: 27). Healthy age matched subjects constituted the control group (Group 2, n: 26). Study group was subdivided into eyes with SEI (Group 1A, 40 eyes) and healthy fellow eyes (Group 1B, 14 eyes). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Accumulation of lymphocytes, macrophages/monocytes, and activated fibroblasts in response to AdV-infected corneal keratocytes is a hallmark histopathological feature of subepithelial (stromal) corneal infiltrates. 110 113 These opacities may persist for up to several weeks to years and have the tendency to result in visual decrease, glare, photophobia, and irregular astigmatism. 3 , 110 Kaye et al 114 used primers for AdV hexon genes to amplify extracted adenoviral DNA from ocular samples of patients who had a history of AdV.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of lymphocytes, macrophages/monocytes, and activated fibroblasts in response to AdV-infected corneal keratocytes is a hallmark histopathological feature of subepithelial (stromal) corneal infiltrates. 110 113 These opacities may persist for up to several weeks to years and have the tendency to result in visual decrease, glare, photophobia, and irregular astigmatism. 3 , 110 Kaye et al 114 used primers for AdV hexon genes to amplify extracted adenoviral DNA from ocular samples of patients who had a history of AdV.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“… 110 113 These opacities may persist for up to several weeks to years and have the tendency to result in visual decrease, glare, photophobia, and irregular astigmatism. 3 , 110 Kaye et al 114 used primers for AdV hexon genes to amplify extracted adenoviral DNA from ocular samples of patients who had a history of AdV. These researchers were able to demonstrate the presence of amplifiable adenoviral DNA in ocular samples, such as tears, indicating that the presence of adenoviral DNA was associated with chronic papillary conjunctivitis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…This study evaluated only corneal aberrations, not total ocular aberrations, since the cornea, which is the first refractive interface, is the most important contributor to the total refractive power of the eye. Kurna et al also measured the effect of persistent corneal subepithelial infiltrates on visual performance and corneal optical quality by using a corneal aberrometry and found that spherical aberration, irregular astigmatism, and total aberration values were significantly higher in eyes with subepithelial infiltrates than in the fellow healthy eyes and control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Persisting sublaminal foci were also observed during chronic infections with HAdV. In these cases, intermittent periods of symptomatic infections are observed, when the risk of virus shedding is higher by definition, thus it is potentially possible to find HAdV DNA in cornea sample of patient with chronic infection, even during asymptomatic phase [Aydin Kurna et al, ]. It is also possible to find HAdV DNA in tear film years after episode of acute conjunctivitis, what may be either an effect of chronic asymptomatic HAdV infection or superinfection with another type of adenovirus, what obviously should be confirmed by HAdV typing [Kaye et al, ].…”
Section: Discussionmentioning
confidence: 99%